Service quality performance of conventional and Islamic banks in Malaysia: an empirical Study - Mohd Shariff, Ros Aniza (2015)
Abstract Purpose-The purpose of this paper is to explore and examine the perceived level of service quality of Islamic and conventional banks in a comparative manner through the perceptions of the customers in Malaysia. This study utilises a modified SERVQUAL model, which is based on the widely accepted SERVQUAL and CARTER model to measure the service quality. Design/ Methodology-Questionnaire survey was utilised with 941 respondents. In analysing the data, descriptive and inferential statistics analyses were employed. Findings- The modified SERVQUAL model seems to provide some guidance regarding how service quality is perceived by bank customers.Result revealed that the expectations of bank customers were not met where the largest gap was obtained in the responsiveness dimension. The factor analysis showed that for expectation of service quality, all the factors could be grouped into four component:‘Operational Services’,‘Social and Islamic Values’,‘Internal Services’ and ‘Appearances’. On the other hand, the factors for perception of service quality are re-classified as:‘Social and Islamic Values’ and ‘Operational and Internal Services’. Research limitations-This exploratory study examines only banks in Malaysia, implying a need for future research conducting this modified model and other methods in other countries. Practical implications- Findings of this study will help the management of the banks in developing their marketing strategy and to become more customer-focused, which is crucial for Malaysian banking in general and for Islamic banking in particular. Social implications- Improved and customized service quality could increases customers’ enthusiasm to deal with the bank on one hand, and raises the productivity of the employees on the other hand. Originality/Value-In addition to the original SERVQUAL model, the modified model used in this study may contribute to service quality measurement in Malaysian dual banking system. Keywords: Malaysia, Customer service quality, Banking, SERVQUAL model, CARTER model.